2007
DOI: 10.1111/j.1741-2358.2007.00138.x
|View full text |Cite
|
Sign up to set email alerts
|

The dental awareness of nursing home staff in Singapore – a pilot study

Abstract: The staff of this nursing home demonstrated positive knowledge of periodontal disease and denture care. However, their knowledge of dental caries revealed substantial room for improvement. This could signal an area for future staff training and development. Such efforts would help establish a team of caregivers who can improve the oral health and quality of life for residents in the nursing home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 9 publications
1
38
2
2
Order By: Relevance
“…Dental caries, a chronic disease is unique among human and is one of the most common important global oral health problem which hinders the acheivement and maintenance of oral health in all age groups in the world today [25] The present study concluded the incidence of dental caries was found to be higher in age group of less than 20 years old.…”
Section: Resultsmentioning
confidence: 48%
“…Dental caries, a chronic disease is unique among human and is one of the most common important global oral health problem which hinders the acheivement and maintenance of oral health in all age groups in the world today [25] The present study concluded the incidence of dental caries was found to be higher in age group of less than 20 years old.…”
Section: Resultsmentioning
confidence: 48%
“…Thean et al [46] completed a pilot self-administered questionnaire for 53 nursing staff in a nursing home to assess their knowledge of dental decay, periodontal disease, and the care of dentures. He found a positive attitude by 99% of the respondents regarding the importance of providing oral care; however, only a third of the staff had received training in oral health and the management of oral care for the nursing home residents.…”
Section: Oral Care Training For Nursing Staffmentioning
confidence: 99%
“…Dental caries is a common and major public health oral disease which hampers the attainment and protection of oral health in different age groups [1,2]. The prevalence pattern and severity of dental caries varies with age, sex, race, socio-demographic characteristics, economic status, geographical location, food practice and oral hygiene habits within the same country or region in various parts of the world [3].…”
Section: Introductionmentioning
confidence: 99%